2013
DOI: 10.2486/indhealth.2012-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Job Strain on Psychological Morbidity and Quality of Life in Military Hospital Nurses in Taiwan: A Follow-up Study

Abstract: This study investigated changes in job strain in female nurses serving in a military hospital system being restructured and the effect of these changes on psychological morbidity and quality of life (QOL). Questionnaire surveys were sent twice to 618 nurses working in three military hospitals in southern Taiwan at the beginning and at follow up a half year later. A Job Content Questionnaire was used to divide subjects into high and low strain groups. The General Health Questionnaire and the WHO QOL Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
0
14
0
4
Order By: Relevance
“…One exception, however, was that female nurses expressed higher levels of CF than the males. In Taiwan, Tzeng, Chung, and Yang () found that the younger nurses reported better satisfaction with work. There are contradicting findings in the literature, which might be related to the interference of other variables, which were not included in these studies, such as relationships with colleagues and managers, financial and marital status, the presence of children, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…One exception, however, was that female nurses expressed higher levels of CF than the males. In Taiwan, Tzeng, Chung, and Yang () found that the younger nurses reported better satisfaction with work. There are contradicting findings in the literature, which might be related to the interference of other variables, which were not included in these studies, such as relationships with colleagues and managers, financial and marital status, the presence of children, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial work factors such as skill level, job strain, work‐life balance, psychological job demand, decision latitude, decision authority and job control can also influence QoL. Psychosocial work factors as a whole affected the QoL of male Malaysian automotive factory workers (Edimansyah, Rusli, Naing, Mohamed, & Winn, ); other studies linked QoL with specific aspects, such as job strain (Lerner, Levine, Malspeis, & D'Agostino, ; Tzeng, Chung, & Yang, ), job control (Liang, Hsieh, Lin, & Chen, ), social support (Jönsson, ; Liang et al., ; Tzeng et al., ), work‐life imbalance (Makabe, Takagai, Asanuma, Ohtomo, & Kimura, ), occupational stress and role overload (Wu, Li, Wang, Yang, & Qiu, ) and imbalanced effort/reward (Teles et al., ). However, promotion of work ability can benefit QoL in physical, psychosocial, social relationship and environmental domains (Milosevic et al., ; Sörensen et al., ) and positive correlations between QoL domains and job satisfactions have also been revealed (Cimete, Gencalp, & Keskin, ; Ibrahim et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A exposição à carga psíquica no trabalho da enfermagem pode estar relacionada com a tensão existente no ambiente de trabalho (10,22,47) e a intensificação do trabalho (36) por meio de exigências cognitivas e emocionais.…”
Section: Categoria 2 -Condições De Trabalho Que Predispõem àS Cargas unclassified
“…Outros fatores estão relacionados com o trabalho noturno, que perturba o equilíbrio oxidanteantioxidante e/ou gera estresse oxidativo (9) nos trabalhadores, assim como o sofrimento (10,14,15,52) , síndrome de Burnout (34,37,40,44,50) entre os profissionais de enfermagem e o aumento do risco de acidentes (21) de trabalho. A implantação de um novo sistema de turnos de trabalho, visando uma melhor distribuição de carga horária, possibilitaria uma redução no número de ausências no trabalho (35) .…”
Section: Categoria 3 -Influências Das Cargas De Trabalho Na Saúde Do unclassified